2019
DOI: 10.1158/0008-5472.can-19-1554
|View full text |Cite
|
Sign up to set email alerts
|

High Levels of C-Reactive Protein Are Associated with an Increased Risk of Ovarian Cancer: Results from the Ovarian Cancer Cohort Consortium

Abstract: Growing epidemiologic evidence supports chronic inflammation as a mechanism of ovarian carcinogenesis. An association between a circulating marker of inflammation, Creactive protein (CRP), and ovarian cancer risk has been consistently observed, yet, potential heterogeneity of this association by tumor and patient characteristics has not been adequately explored. In this study, we pooled data from casecontrol studies nested within six cohorts in the Ovarian Cancer Cohort Consortium (OC3) to examine the associat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 59 publications
1
30
0
Order By: Relevance
“…In EOC, CRP has been consistently associated with risk , with a recent meta-analysis 29 noting that EOC risk rises with increasing CRP concentration, and the risk of EOC in women with CRP concentrations greater than 10 mg/L was more than doubled. Our cut-off value of CRP for EOC was 9.8 mg/L, which is consistent with the results of previous studies that showed a high-risk predictive value of CRP for EOC at 10 mg/L 30 , 31 . However, small sample size leads to imprecision in estimates of performance, and therefore sample sizes should be increased in future research.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In EOC, CRP has been consistently associated with risk , with a recent meta-analysis 29 noting that EOC risk rises with increasing CRP concentration, and the risk of EOC in women with CRP concentrations greater than 10 mg/L was more than doubled. Our cut-off value of CRP for EOC was 9.8 mg/L, which is consistent with the results of previous studies that showed a high-risk predictive value of CRP for EOC at 10 mg/L 30 , 31 . However, small sample size leads to imprecision in estimates of performance, and therefore sample sizes should be increased in future research.…”
Section: Discussionsupporting
confidence: 92%
“…There is no evidence that CRP promotes the development of cancer, but the increase in circulating CRP with the onset of EOC may be caused by inflammation in the tumor microenvironment 16 , and inflammation is believed to exert carcinogenic actions 40 . Inflammation directly participates in tumor development by generating toxic oxidants and biologically active substances, and these may damage DNA and proteins, thereby increasing the possibility of mutagenesis 30 . In the microenvironment surrounding tumor formation, ovarian surface epithelium may therefore be continuously exposed to an inflammatory environment in which CRP upregulation follows activation of the proinflammatory factors interleukin-6 (IL-6) and tumor necrosis factor-alpha (TNF-α) 40 .…”
Section: Discussionmentioning
confidence: 99%
“…The level of these cytokines in the serum of OC patients is associated with poorer prognosis 58–60 . High levels of IL‐6 or TNF in ascites is associated with shorter progression‐free survival 58,60 and circulating CRP levels are associated with increased risk of ovarian cancer 61,62 …”
Section: Ovarian Cancermentioning
confidence: 99%
“…Second, therapeutics could be used to reduce inflammation during the disease course or treatment of cancer to improve outcomes. For example, low dose aspirin, a Cox1/2 inhibitor, is protective against ovarian cancer, leading to both a reduced risk 128,129 and better prognosis 62 . This may in part be due to a decrease in chronic inflammation leading to an increase in protective T cell responses.…”
Section: The Combined Impact Of Ageing‐ Cancer‐ and Treatment‐derivmentioning
confidence: 99%
“…Recent evidence supports chronic in ammation (CRP values over 10 mg/L) as a mechanism of ovarian carcinogenesis (57). Interestingly, one study (57) showed that ever users of OC had an increased risk for ovarian cancer (OR=3.24, 95%CI=1. 62-6.47).…”
Section: C-reactive Proteinmentioning
confidence: 99%